The impact of social isolation on cardiovascular disease in the elderly: a systematic review - Marsim, Etanaulia; Salsabil, Husna Arwa; Dwiyovita, Rizka (Universitas 'Aisyiyah Yogyakarta, 2025)
Social isolation can increase mortality and most likely have an impact on health. The impact of social isolation and loneliness on health and well-being is recognised globally as a public health problem. Social isolation can be experienced at any age, especially in the elderly. The purpose of this study was to determine the effect of social isolation on the occurrence of cardiovascular disease in the elderly. This study is a systematic review. Article searches are conducted through databases: PubMed, Science Direct, and Google Scholar with the keywords used in article searches are as follows